Manufacturing ideology : Scientific management in twentieth-century Japan - Tsutsui, William M. (Princeton University Press, 1998)
Japan's management style is often praised as uniquely efficient and humane, rooted in its culture. However, Tsutsui argues it's largely based on American "Taylorism," adapted due to Japan's economic constraints. Lacking resources for full "Fordism," Japan modified Taylorism to suit its needs. This revised model, supported by the government, challenges myths of a purely Japanese management ideology.